For those who hunt the wounded down a novel - Richards, David A. (McClelland & Stewart, 1993)
"This brilliant conclusion to the trilogy which began with Nights Below Station Street is ultimately hopeful, as the new generation looks back at the past and its heroes with a sense of warning, but also of love."--BOOK JACKET